Top gun [videorecording (DVD)] - Scott, Tony, 1944-2012; Cruise, Tom, 1962-; McGillis, Kelly, 1957-; Kilmer, Val, 1959- (Paramount, 2004)
At the elite Navy Fighter Weapons School, cocky, young pilots compete against one another in the air as well as on the ground.